Pancreas-Brain Crosstalk - Battuvshin Lkhagvasuren; Onanong Mee-inta; Zi-Wei Zhao; Tetsuya Hiramoto; Damdindorj Boldbaatar; Yu-Min Kuo; Yu-Min Kuo (Frontiers Media S.A., 2021)
The neural regulation of glucose homeostasis in normal and challenged conditions involves the modulation of pancreatic islet-cell function. Compromising the pancreas innervation causes islet autoimmunity in type 1 diabetes and islet cell dysfunction in type 2 diabetes. However, despite the richly innervated nature of the pancreas, islet innervation remains ill-defined. Here, we review the neuroanatomical and humoral basis of the cross-talk between the endocrine pancreas and autonomic and sensory neurons. Identifying the neurocircuitry and neurochemistry of the neuro-insular network would provide clues to neuromodulation-based approaches for the prevention and treatment of diabetes and obesity.